The Influence of Health Education About Complementary Foods for Breast Milk (MPASI) on the Knowledge and Attitudes of Mothers of Babies Aged 0-6 Months - Rismawati, Sariestya; Kurnia, Herni (Poltekkes Kemenkes Tasikmalaya, 2025)
Background: Infant development and growth are natural processes that can be supported by good nutrition coverage. Providing complementary foods for breast milk is an effective way to improve development and infant growth since the age of 6 months. However, in reality, there are still many mothers who do not know about infant nutritional needs causing infant nutritional needs to be unmet. Therefore, health education is very important to improve mothers' knowledge and attitudes so that infant nutritional needs are met. Objective: To determine the effect of health education about complementary foods for breast milk on the knowledge and attitudes of mothers of infants aged 0-6 months. Method: This study used a pre-experimental one-group pre-test post-test design method. The population in this study were mothers who had infants aged 0-6 months total of 29 people. The sampling technique used a purposive sampling technique total of 25 people. The collection of research data was carried out by distributing questionnaires 2 times, namely before health education (pre-test) and after health education (post-test). The data analysis technique used univariate tests and the Paired Sample T-test. Results: The results of the study before health education were given showed that the majority of mothers' knowledge regarding the provision of complementary foods was in the sufficient category, namely 14 people (56%), while the majority of mothers' attitudes were in the positive category, namely 15 people (60%). After being given health education, the mothers' knowledge regarding the provision of complementary foods increased to the good category, namely 20 people (80%), and positive category attitude, namely 23 people (92%). Conclusion: From the results of the study, it can be concluded that health education greatly influences the increase in mothers' knowledge and attitudes regarding complementary foods.